Serum levels of immunoglobulins and severity of community-acquired pneumonia. Issue 1 (28th November 2016) - de la Torre, Mari C; Torán, Pere; Serra-Prat, Mateu; Palomera, Elisabet; Güell, Estel; Vendrell, Ester; Yébenes, Joan Carles; Torres, Antoni; Almirall, Jordi
Abstract : Instruction: There is evidence of a relationship between severity of infection and inflammatory response of the immune system. The objective is to assess serum levels of immunoglobulins and to establish its relationship with severity of community-acquired pneumonia (CAP) and clinical outcome. Methods: This was an observational and cross-sectional study in which 3 groups of patients diagnosed with CAP were compared: patients treated in the outpatient setting (n=54), patients requiring in-patient care (hospital ward) (n=173), and patients requiring admission to the intensive care unit (ICU) (n=191). Results: Serum total IgG (and IgG subclasses IgG1, IgG2, IgG3, IgG4), IgA and IgM were measured at the first clinical visit. Normal cutpoints were defined as the lowest value obtained in controls (≤680, ≤323, ≤154, ≤10, ≤5, ≤30 and ≤50 mg/dL for total IgG, IgG1, IgG2, IgG3, IgG4, IgM and IgA, respectively). Serum immunoglobulin levels decreased in relation to severity of CAP. Low serum levels of total IgG, IgG1 and IgG2 showed a relationship with ICU admission. Low serum level of total IgG was independently associated with ICU admission (OR=2.45, 95% CI 1.4 to 4.2, p=0.002), adjusted by the CURB-65 severity score and comorbidities (chronic respiratory and heart diseases). Low levels of total IgG, IgG1 and IgG2 were significantly associated with 30-day mortality. Conclusions: Patients with severe CAP admitted to the ICU showed lower levels of immunoglobulins than non-ICU patients and this increased mortality.